2019
DOI: 10.1093/gerona/glz123
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Scales of Frailty and Physical Performance Improves Prediction of Major Adverse Cardiac Events in Older Adults with Acute Coronary Syndrome

Abstract: Background The number of older adults admitted to hospital for acute coronary syndrome (ACS) has increased worldwide. The aim of this study was to determine which scale of frailty or physical performance provides incremental improvements in risk stratification of older adults after ACS. Methods A prospective cohort of 402 older (≥70 years) ACS patients were enrolled. Data about baseline characteristics, Global Registry of Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…The manifestations of frailty are associated with damage to the vital functional reserve systems that control hormones, immune, inflammatory and neural processes. 29 Previous studies have shown that frailty has predictive value of mortality in ACS patients. 13,30 And our previous studies demonstrated that indicators associated with multiple pathophysiological states involved in the pathogenesis of cardiovascular disease might provide more prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of frailty are associated with damage to the vital functional reserve systems that control hormones, immune, inflammatory and neural processes. 29 Previous studies have shown that frailty has predictive value of mortality in ACS patients. 13,30 And our previous studies demonstrated that indicators associated with multiple pathophysiological states involved in the pathogenesis of cardiovascular disease might provide more prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that this might be useful in the clinical decisionmaking process. 27 Even non-cardiovascular comorbidities (NCC) like diabetes, renal disease or anemia can provoke worse outcomes. Ofori-Asenso et al showed in 1488 older adults hospitalized for NSTE-ACS that having ≥2 NCC was associated with a significantly increased likelihood of longer hospital stays and in-hospital death rates (HR 1.79, 95% CI: 1.06-3.03; p=0.029), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Data are lacking regarding death, MI, stroke, and revascularization at 1 year in patients ≥75 years with MI and MVD treated with culprit-only revascularization. Taking into account available ( Table I ) and recently published data, 46 , 47 we estimated a conservative 15% rate of the primary end point (POCE) at 1 year in the culprit-only strategy group. We hypothesize that the functional assessment should reduce the primary end point by at least 30% ( Table II ).…”
Section: Methodsmentioning
confidence: 99%